THE TEST PROGRAMME CONCERNING AIRCRAFT POSITIONING AND TRAFFIC MONITORING – PART I - Henryk JAFERNIK (Scientific Journal of Silesian University of Technology. Series Transport)
The article presents results of the researches of the range to determine of the transmission’s data with using of the standard modems UHF Satellite on the transmission frequency of the 460 MHz and the regulating power 1-10W. Because of this reason there was created programme of the researches in the air. The researches revealed the possibility increase a range of monitoring and coordination of the airships on the distance of 80-120 km.